Prevalence of Intestinal Parasites and Associated Factors Among Public Primary Second‐Cycle Schoolchildren in Debre Markos Town, Northwest Ethiopia: A Cross‐Sectional Study - Abtie Abebaw; Gebreselassie Demeke; Hylemariam Mihiretie Mengist; Mengistu Endalamaw; Gizew Damtie Demeke (Health Science Reports)
ABSTRACT Background and Aims Intestinal parasitic infection is a common disease that causes significant morbidity and mortality in developing countries, including Ethiopia. The burden of intestinal parasites is worse in schoolchildren, which leads to absenteeism from school, lower cognitive ability, affects academic performance, and causes malnutrition and anemia. While many studies have been reported, there is a paucity of published data in Debre Markos. Therefore, this study aimed to assess the prevalence of intestinal parasites and associated factors among public primary second‐cycle schoolchildren in Debre Markos Town, Northwest Ethiopia. Methods A school‐based cross‐sectional study was conducted among three selected public primary second‐cycle schools in Debre Markos town from May 1 to 30, 2022. Study participants were selected by using random and systematic sampling techniques with proportional allocation to each grade. Data were collected using semi‐structured questionnaires. A single stool specimen was collected from the study participants and processed using direct wet mount and formol ether concentration technique. Binary logistic regression models were applied to assess the association between independent and outcome variables at a 95% confidence level. Results A total of 343 students were included in the study. The overall prevalence of intestinal parasites was 12% (41/343) with a predominance of hookworms (5.2%, 18/343), followed by Ascaris lumbricoides 2.3% (8/343), Entamoeba histolytica/dispar 1.2% (4/343), Hymenolepis nana 0.9% (3/343), Strongyloides stercoralis 0.9% (3/343), Giardia lamblia 0.9% (3/343), and Trichuris trichiura 0.6% (2/343). The habit of open‐field defecation (AOR, 95% CI; 2.43 [1.16–5.09]), not using soap to wash hands (AOR, 95% CI; 2.93 [1.33–6.42]), and not wearing closed shoes (AOR, 95% CI; 3.12 [1.19–8.23]) were factors significantly associated with the prevalence of intestinal parasitic infection. Conclusion The prevalence of intestinal parasites was comparatively low in the study area. Open‐field defecation, not using soap to wash hands, and not wearing closed shoes were identified as independent predictors.